CURRENT SYSTEM OF FINANCIAL SUPPORT SUBJECTS MICRO-ENTREPRENEURSHIP IN THE UAE - T. Dabbous (Вестник университета)
The article assesses the current system of financial support of subjects of micro-enterprises in the Unated Arab Emirates (UAE). The sources of funding of financial resources for the development of microenterprises are considered. It is established that in the UAE several sources of formation of financial resources are available to micro-enterprises development, including public foundations, the agencies of support of small and medium business, commercial banks, credit agencies, crowd funding. The government of the UAE seeks to provide the conditions contributing to effective development of micro-enterprises.